Hubungan Kualitas Program Siaran dengan Aspek Kognitif Pendengar Radio - Dias Arliadini; Nova Yuliati (Bandung Conference Series: Public Relations, 2022)
Abstract. The quality of broadcast programs is one of the factors that can influence audiences to be interested in programs made by radio stations. Broadcast programs must always be directed and made according to the needs of the community, one of which is the needs of the cognitive aspects of the audience. How the mass media (radio) will help the audience to get and understand any information it receives. The purpose of this study was to determine the relationship between the quality of broadcast programs which include compatibility, consevation of program resources, and breadth of appeal of the "Geng Sore" program with cognitive aspects of listeners of Radio MGT 101.1 FM. This study uses a quantitative approach with a correlational method. The sample taken in this study was 97 respondents, who were selected using random sampling technique and calculated based on the Slovin formula. The theory used in this research is the S-O-R theory. The data collection technique used is by using a questionnaire which will be distributed via google formular to the respondents. The data analysis technique used is statistical analysis using rank sprearman correlation. From the results of this study, it is known that there is a high/strong relationship between the quality of broadcast program and the cognitive aspects of listeners of MGT Radio 101.1 FM Bandung, with the calculation result of a correlation of 0.747. Abstrak. Kualitas program siaran merupakan salah satu faktor yang dapat mempengaruhi khalayak untuk tertarik dengan program yang dibuat oleh staisun radio. Program siaran harus selalu diarahkan dan dibuat dengan menyesuaikan kebutuhan masayarakat, salah satunya pada kebutuhan aspek kognitif khalayak. Bagaimana media massa (radio) ini, akan membantu khalayak untuk mendapatkan serta memahami setiap informasi yang diterimanya. Tujuan dari penelitian ini adalah untuk mengetahui adanya hubungan antara kualitas program siaran yang meliputi kesesuaian program, pemeliharaan sumber daya program, dan daya tarik pada program “Geng Sore” dengan aspek kognitif dari pendengar Radio MGT 101.1 FM. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel yang diambil dalam penelitian ini sebanyak 97 responden, yang dipilih dengan menggunakan teknik random sampling dan dihitung berdasarkan rumus Slovin. Teori yang digunakan dalam penelitian ini adalah teori S-O-R. Teknik pengumpulan data yang digunakan yaitu dengan menggunakan kuesioner yang akan disebarkan melalui google formular kepada para responden. Teknik analisis data yang digunakan adalah analisis statistika dengan menggunakan korelasi rank sprearman. Dari hasil penelitian ini, diketahui bahwa terdapat hubungan yang tinggi/kuat antara kualitas program siaran “Geng Sore” dengan aspek kognitif pendengar MGT Radio 101.1 FM Bandung, dengan hasil perhitungan korelasi sebesar 0,747.